In-situ microbially induced Ca2+-alginate polymeric sealant for seepage control in porous materials - Cheng, Liang (2019)
This paper presents a novel approach of using in‐situ microbially induced Ca2+‐alginate polymeric sealant for seepage control in porous materials. This process comprises two steps: (i) generation of insoluble calcium carbonate inside the pores of porous materials (such as sand) through a microbially induced carbonate precipitation (MICP) process in‐situ and (ii) injection of sodium alginate for in‐situ gelation via reaction between alginate and Ca2+ ions. The experimental results showed that the hydraulic conductivity/permeability of sand decreased with the increase in alginate concentration. When 5% alginate was used with a CaCO3 concentration of 0.18 g g−1 sand, the permeability of the alginate‐treated sand reduced from 5.0 × 10−4 to 2.2 × 10−9 m s−1. The scanning electron microscopy images revealed that a film‐type coating was formed around sand particles with spherical round crystals embedded. Furthermore, the in‐situ formed Ca‐alginate polymeric sealant can also be used for the removal of Cu2+ ion and suspended particles from contaminated water by more than 90%. Built on the current research, the envisioned practical application of the proposed method may include clogging fractured rock, reducing seepage and prevent piping through dams, excavation dewatering, and forming barriers for remediating specific contaminants.